Vestibular characterization in the menstrual cycle - Ishii,Cintia (2009)
Hormonal disorders in the menstrual cycle can affect labyrinthine fluid homeostasis, causing balance and hearing dysfunctions. STUDY DESIGN: Clinical prospective. AIM: compare the results from vestibular tests in young women, in the premenstrual and postmenstrual periods. MATERIALS AND METHODS: twenty women were selected with ages ranging from 18 to 35 years, who were not using any kind of contraceptive method for at least six months, and without vestibular or hearing complaints. The test was carried out in each subject before and after the menstrual period, respecting the limit of ten days before or after menstruation. RESULTS: there was a statistically significant difference in the menstrual cycle phases only in the following vestibular tests: calibration, saccadic movements, PRPD and caloric-induced nystagmus. We also noticed that age; a regular menstrual cycle; hearing loss or dizziness cases in the family; and premenstrual symptoms such as tinnitus, headache, sleep disorders, anxiety, nausea and hyperacusis can interfere in the vestibular test. CONCLUSION: there are differences in the vestibular tests of healthy women when comparing their pre and postmenstrual periods.